A Study of Drugs Causing Fixed Drug Eruptions - Rahman, Md Moksedur; Abdullah, Md; Nessa, Moriom; Siddique, Muhammad Afsar; Hossain, Md Moazzem; Rahman, Md Khalilur; Khan, MMR (TAJ: Journal of Teachers Association, 2018)
Fixed drug eruption (FDE) is a distinctive type of cutaneous drug reaction that characteristically recurs in the same site or sites each time a particular drug is taken. FDEs are among the most frequent problems encountered by the dermatologists. The present study was carried out to recognize offending drugs, to educate the patients and to avoid self-administration of drugs and re-administration of the offending drugs. The study was conducted in Skin & VD outpatient department of Rajshahi Medical College Hospital, Rajshahi over a period of one year. One hundred ten cases with established FDE were evaluated clinically. The causative drugs were identified and confirmed by provocation tests. Cotrimoxazole (25%) was the most common cause of FDE. Other drugs incriminated were NSAID (21.8%), Tetracycline (15.4%), Ciprofloxacin (10%), Amoxicillin (7.2%), Metronidazole (5.4%), Griseofulvin (2.7%) and Fluconazole (1.8%). The lesions were found to be distributed on the oro-genital mucosa, trunk and the acral regions.The main presentation of FDE was circularhyperpigmented lesion. TAJ 2014; 27(1): 29-33